Missional branding: A case study of the Church of Pentecost - White, Peter (HTS teologiese studies, 2019)
Branding is a strategy designed by companies to help patrons or consumers quickly identify their products or organisations and give them a reason to choose their products or organisations over other competitors. In the Old Testament, God identified the Israelites as a unique brand. In the New Testament, Jesus Christ branded the church with the power of the Holy Spirit, miracles, signs and wonders. Reading the Acts of the Apostles, the church developed a brand of being Spirit-filled, communal-living and mission-minded. It was out of this that early believers in Antioch were called ‘Christians’. The name ‘Christian’ therefore became a brand name for believers and followers of Jesus Christ. In view of this, one would expect that the concept of branding would be a major tool for modern-day churches. Although there are several publications on branding from the perspective of marketing and management, there is no such academic research on missional branding, hence this research. This article contributes to the interdisciplinary discourse on branding, with specific reference to the missional branding of the Church of Pentecost.